The Marsh King's daughter [videorecording (Blu-Ray + DVD)] - Smith, Elle; Smith, Mark L.; Ridley, Daisy, 1992-; Mendelsohn, Ben; Hedlund, Garrett, 1985-; Pistorius, Caren; Prince, Brooklynn, 2010-; Birmingham, Gil; Bzowski, Adam Janota; Dionne, Karen (Roadside Attractions ; Lionsgate, 2024)
When her father, the Marsh King, escapes from prison, Helena must rely on all her survival skills to confront him for all the years he kept her and her mother captive in the wilderness.